The Effectiveness of Animation Videos on Knowledge of Prospective Brides in Efforts to Prevent Stunting - Mega, Mega; Ulfah, Erliana; Solihah, Rosidah (Yayasan Inspirasi El Burhani, 2024)
Introduction: According to data from the World Health Organization (WHO), stunting is the highest prevalence in the Southeast Asia region (SEAR), one of which is Indonesia. Efforts to prevent stunting start from preconception, by providing knowledge and understanding regarding fulfilling nutritional intake before pregnancy. Objective: This research aims to analyze the effectiveness of using animated videos on the knowledge of prospective brides and grooms in efforts to prevent stunting in, Darmaraja District, Sumedang Regency. Method: The research method is quantitative with a quasi-experiment in the form of a pretest and posttest design. The sample consisted of 102 people. Consecutive sampling research. Research in September-November 2023. Data analysis using the Mann-Whitney test. Result: The research results showed that the pretest intervention group's knowledge was 76%, and post-test the use of animated videos was 88% with a value of p=0.002 (p<0.05). The effectiveness of animated videos with N-Gain is 60.1%, meaning it is quite effective. Conclusion: Animated videos increase the knowledge of prospective brides and grooms in preventing stunting and animated videos are effective in increasing the knowledge of prospective brides and grooms in efforts to prevent stunting in Darmaraja District, Sumedang Regency.